Towards Localization of Automated Tutors for Developing Countries - Zualkernan, Imran; Arroyo, Ivon; Woolf, Beverly P. (2013)
Abstract. This paper describes localization issues in relation to AIED systems in the developing world, and analyzes the particular case of the successful immersion of learning technologies to schools in Pakistan. The paper analyzes the needs for personalized learning in the developing world in comparison to countries such as the United States. A model and a survey based on various types of localization dimensions like teacher, student, and cultural alignment was developed and deployed to conduct an evaluation of an AI tutor called the Wayang Outpost in Pakistan. The results are that teachers are likely to use such a system if available, and that their intention to use such a tutor in the future is strongly dependent on how well the tutor is aligned with their teaching practices, students ’ learning habits, and whether the language in the tutor is understood by students. On average these teachers were also willing to allocate about two hours per week for such automated tutors.
KerkoCite.ItemAlsoKnownAs: 2339240:BSFMA2FT 2405685:CZR7Q4AJ
Keywords: ⛔ No DOI found

Growth Mindset Predicts Student Achievement and Behavior in Mobile Learning - Kizilcec, René F.; Goldfarb, Daniel (Proceedings of the Sixth (2019) ACM Conference on Learning @ Scale, 2019)
Students’ personal qualities other than cognitive ability are known to influence persistence and achievement in formal learning environments, but the extent of their influence in digital learning environments is unclear. This research investigates non-cognitive factors in mobile learning in a resourcepoor context. We surveyed 1,000 Kenyan high school students who use a popular SMS-based learning platform that provides formative assessments aligned with the national curriculum. Combining survey responses with platform interaction logs, we find growth mindset to be one of the strongest predictors of assessment scores. We investigate theory-based behavioral mechanisms to explain this relationship. Although students who hold a growth mindset are not more likely to persist after facing adversity, they spend more time on each assessment, increasing their likelihood of answering correctly. Results suggest that cultivating a growth mindset can motivate students in a resource-poor context to excel in a mobile learning environment.
KerkoCite.ItemAlsoKnownAs: 10.1145/3330430.3333632 2339240:L3XGQDF9 2405685:WYTNLMM6

Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1) - Haßler, Björn; Brugha, Meaghan; Muyoya, Chisenga; Mitchell, Joel; Hollow, David; Jackson, Alan (Jigsaw and Open Develoment & Education, 2018)
Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1) Also available at https://digitalprinciples.org/resource/donor-organizations-the-principles-for-digital-development-a-landscape-assessment-and-gap-analysis/, https://digitalprinciples.org/wp-content/uploads/PDD2018_interactive.pdf
EdTechHub.Source: 2129771:I2CG3TP3 shortDOI: 10/ghgk6z KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.1204703 10/ghgk6z 2129771:I2CG3TP3 2129771:SI7RBL6P 2405685:46SDL9HI
Keywords: _DOILIVE; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode